Managing acid soils for reclaiming livelihoods in Ethiopia - Amede, Tilahun; Schulz, S.; Warner, James; Tefera, Solomon (2019)
Soil acidification is the result of a complex set of processes caused both naturally and by human activity. It limits plant growth because of conditions that increase base element deficiencies, Phosphorus-fixation and toxicities of Aluminum, Manganese and Hydrogen ions.